If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + 15 = -4y + -11 Reorder the terms: 15 + -6y = -4y + -11 Reorder the terms: 15 + -6y = -11 + -4y Solving 15 + -6y = -11 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 15 + -6y + 4y = -11 + -4y + 4y Combine like terms: -6y + 4y = -2y 15 + -2y = -11 + -4y + 4y Combine like terms: -4y + 4y = 0 15 + -2y = -11 + 0 15 + -2y = -11 Add '-15' to each side of the equation. 15 + -15 + -2y = -11 + -15 Combine like terms: 15 + -15 = 0 0 + -2y = -11 + -15 -2y = -11 + -15 Combine like terms: -11 + -15 = -26 -2y = -26 Divide each side by '-2'. y = 13 Simplifying y = 13
| 5x^2-20x-40=0 | | .4u+6=10 | | v(v+2)=15 | | -24=6x | | a^4=a^3-30a^2 | | a^4=7a^3-30a^2 | | x(x-15.50)=47.5 | | 30=-10v | | 10-(4x-3)=7-5x | | 8x-7=5+20 | | 75=5u | | -30=-10y | | 6(y-1)=5(y-4) | | h(x)=-[[x]] | | p(5)=p-4(20) | | 15.50(x-15.50)=47.50 | | -324=-18c | | -12x-10(5x+27)=-22 | | 91=7w | | -5x+4=-16 | | p/20=p-4/5 | | 5x-4-x=-4 | | 57=3v | | -8(w+9)-(-5w-5)=-4w | | 50x+8=96 | | -24=3v | | n^2=4n-2 | | -143+7x=-4x+55 | | -7x-2=-23 | | 9(c-3)=2+8c | | 47.50-x=x+15.50 | | 5(x+2)-4(x+3)= |